REAKSI PASAR SEBELUM DAN SESUDAH PENGUMUMAN RIGHT ISSUE - Aryasa, I Putu Gde Chandra Artha; Suaryana, I G N Agung (E-Jurnal Akuntansi; Vol 18 No 2 (2017), 2017)
The purpose of this study are to examine differences in market reaction before and after the announcement of the rights issue. Right issue a new share issue carried out by the company which the rights to buy new shares granted to existing shareholders. This research was conducted on all companies listed in Indonesia Stock Exchange 2010-2015 period. The sampling method using purposive sampling. The number of samples of this research were 79 companies. Tests carried out on the sample overall, based on company size, and based on the intended use of funds. The results show the differences in abnormal return before and after the announcement of the rights issue for overall sample and the sample group investment purposes. Results for sample group based on company size and sample group debt payment purposes no differences abnormal return before and after the announcement of rights issue.
Keywords: right issue, market reaction, abnormal return, company size, the intended use of funds